The Post-Colonial Security Dilemma : Timor-Leste and the International Community - Strating, Rebecca (Book collections on Project MUSE., 2019)
This book examines the development of Timor-Leste's foreign policy since achieving political independence in 2002. It considers the influence of Timor-Leste's historical experiences with foreign intervention on how the small, new state has pursued security. The book argues that efforts to secure the Timorese state have been motivated by a desire to reduce foreign intervention and dependence upon other actors within the international community. Timor-Leste's desire for 'real' independence -- characterized by the absence of foreign interference -- permeates all spheres of its international political, cultural and economic relations and foreign policy discourse. Securing the state entails projecting a legitimate identity in the international community to protect and guarantee political recognition of sovereign status, an imperative that gives rise to Timor-Leste's aspirational foreign policy. The book examines Timor-Leste's key bilateral and multilateral diplomatic relations, its engagement with the global normative order, and its place within the changing Asia-Pacific region.